ผลของการปฏิบัติสมาธิของผู้เรียนหลักสูตรครูสมาธิ สถาบันพลังจิตตานุภาพ สาขา 97 วัดศรีทีปาราม จังหวัดเลย - ปสนฺนจิตฺโต, พระวิสันต์ (วารสารศรีล้านช้างปริทรรศน์, 2021)
บทความเรื่องนี้มีวัตถุประสงค์เพื่อ (1) ศึกษาผลของการปฏิบัติสมาธิของผู้เรียนหลักสูตรครูสมาธิ สถาบันพลังจิตตานุภาพ สาขา 97 วัดศรีทีปาราม จังหวัดเลย และ (2) เปรียบเทียบเพื่อศึกษาผลของการปฏิบัติสมาธิของผู้เรียนหลักสูตรครูสมาธิ สถาบันพลังจิตตานุภาพ สาขา 97 วัดศรีทีปาราม จังหวัดเลย จำแนกตาม เพศ และอายุ ที่ต่างกัน ประชากรศึกษาคือ ผู้เรียนหลักสูตรครูสมาธิ สถาบันพลังจิตตานุภาพ สาขา 97 วัดศรีทีปาราม จังหวัดเลย รุ่น 47 สัตตจัตตาฬีสโม (สิริญาณ) จำนวน 37 คน เครื่องมือที่ใช้ในการศึกษา ใช้แบบสอบถาม ประมาณค่า 5 ระดับ ใช้สถิติในการวิเคราะห์ข้อมูล คือ ค่าร้อยละ ค่าความถี่ ค่าเฉลี่ย และค่าส่วนเบี่ยงเบนมาตรฐาน             ผลการวิจัยพบว่า ผลของการปฏิบัติสมาธิของผู้เรียนหลักสูตรครูสมาธิ สถาบันพลังจิตตานุภาพ สาขา 97 วัดศรีทีปาราม จังหวัดเลย โดยรวมทั้ง 3 ด้าน อยู่ในระดับมากที่สุด และเมื่อพิจารณาเป็นรายด้าน พบว่า ด้านที่มีค่าเฉลี่ยสูงที่สุดคือ ด้านสังคม ด้านจิตใจ และด้านกายที่อยู่ในระดับมาก ตามลำดับ สำหรับการเปรียบเทียบผลของการปฏิบัติสมาธิของผู้เรียนหลักสูตรครูสมาธิ สถาบันพลังจิตตานุภาพ สาขา 97 วัดศรีทีปาราม จังหวัดเลย จำแนกตามเพศ พบว่า เพศหญิงสูงกว่าเพศชาย และจำแนกตามอายุ พบว่า อายุ 30 – 59 ปี มีค่าเฉลี่ยสูงที่สุด รองลงมา คือ อายุ 60 ปีขึ้นไป และอายุต่ำกว่า 30 ปี ตามลำดับ Abstract                The objectives of the research article were (1) to study the effects of meditation on practitioners in the meditation instructor course organized by the Willpower Institute Branch 97 at Sridiparam Temple, Loei province, and (2) to compare the effects of meditation on practitioners in the meditation instructor course organized by the Willpower Institute Branch 97 at Sridiparam Temple, Loei province, classified by gender and age. The population of the research was a total of thirty-seven practitioners in the 47 th Class of the meditation instructor course, organized by the Willpower Institute Branch 97 at Sridiparam Temple, Loei province. The instrument used for data collection was the five-point rating scale questionnaire; the statistics used for data analysis comprised of percentage, frequency, mean, and standard deviation.                The results of the research revealed that the meditation effects on practitioners in the meditation instructor course conducted by the Willpower Institute Branch 97 at Sridiparam Temple, Loei province was found to be overall at the highest level. Separately considered in the descending order, the aspects with the high level of mean scores were society, mentality, and physicality, respectively. The comparison of meditation effects on practitioners in the Willpoper Institute’s meditation instructor course at Sridiparam Temple, Loei province, classified by gender, was found that the effects on women were higher than on men; the effects on ones with 30-59 years of age were found at the highest level of mean scores, followed by ones with over 60 years and ones with lower 30 years, respectively.